The Phenomenon of Fear of Missing Out (FoMO) in West Sumatra PTKIN Students - Desmita Desmita; Eliwatis Eliwatis; Romi Maimori; Suci Shawmy Febrita (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
The digital era that makes it easier for humans to do activities and communicate makes every day use smartphones. Students use the internet as a way to find information, besides that it also provides an opportunity for each student to see other people's activities which are considered more valuable than their own experiences, causing anxiety and fear for themselves when not involved in social media called FoMO (Fear of Missing Out). This study aims to determine the condition of FoMO in students living in Ma'had Al-Jami'ah PTKIN West Sumatra, using a mix method by combining quantitative and qualitative methods to understand research problems The sampling technique in this study was total sampling with a total sample of 80 people living in Ma'had. The measuring instrument used in this study is the scale of the adaptation of the FoMO scala by Przybyski, et al (2013). The results of this study indicate that in general they are in the high category, which means that students are less able to control feelings of anxiety, fear, worry about losing precious moments without their involvement in the media.